Study on interfacial mechanical properties and structural detail damage of CRTS II slab ballastless track - Anxiang Song; Guowen Yao; Yuanchen Guo; Gaofeng Zhang; Xuanrui Yu (Scientific Reports, 2024)
Abstract The CRTS (China Railway Track System) II slab ballastless track is widely utilized in high-speed railway construction owing to its excellent structural integrity. However, its interfacial performance deteriorates under high-temperature conditions, leading to significant damage in structural details. Furthermore, the evolution of its performance under these conditions has not been comprehensively studied. In this study, a bilinear cohesive damage model was developed using positive tensile and push-out model tests to describe the interfacial mechanical behavior of the track structure. A three-dimensional refined numerical simulation model of the CRTS II slab ballastless track was developed and validated using existing test data to analyze the distribution of structural damage and its evolution under varying temperature conditions. The results demonstrate that the proposed bilinear cohesive damage model effectively characterizes the interlayer damage evolution in the track structure. As the overall temperature increases, interlayer separation initiates at the wide-narrow joints and propagates from the slab ends toward the center. At a temperature rise of 60 °C, the interface becomes fully separated, and the vertical displacement of the wide-narrow joints and the track slab reaches 1.09 cm. The middle and end sections of the wide joints are particularly susceptible to compressive damage, with the top section being more sensitive to temperature changes. These results provide critical insights into the damage mechanisms and performance evolution of ballastless tracks under thermal loading, offering a foundation for improved design and maintenance strategies.